INTERFACES BETWEEN PUBLIC AND PRIVATE IN HIGHER EDUCATION: PROSPECTIVE VIEWS ABOUT PUBLIC COMMUNITY EDUCATION NON-STATE OF LUTHERAN IDENTITY IN BRAZIL - Ahlert, Alvori (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2011)
This paper presents a literature search on the relationship between public and private in the recent history of Brazilian higher education with the goal of a prospective outlook for community education of Lutheran identity. It presents an analysis of some references to the design of community education in the context of public higher education, which evolved into the understanding of community education non-State public and their meanings and responsibilities as an interface between public and private education. Whose discussion is presented at the third time this text. With a prospective outlook, points to the potential of non-state public education into the context of the institutions identified with the Lutheran identity.